Peranan Pondok Pesantren Dalam Upaya Pemberdayaan Masyarakat (Studi Pada Pondok Pesantren di Jombang) - Machin, H.; Supriyadi, H. (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2016)
The purpose of this study was to determine the role of the boarding school in an effort to increase community empowerment. Islamic boarding school. The data used is qualitative data using questionnaires distributed to respondents. The results of this study are of determination test shows that the strategic role of schools namely: scientific, entrepreneurial spirit and work ethic / independence provide a significant contribution to the empowerment of alumni in Ponpes Roudlotu Qur'an Perak Jombang Tahfizdil of 97.3%, while the remaining amount 2.7% is explained by other variables outside of this study were not included in this research model. From some students who have finished studying, which are engaged in the fields of science (becoming educators), entrepreneurship (to be entrepreneurs or self-employed) and be an employer / employee (related to work ethic and independence). Variable strategic role of schools in the form of science (X1)the dominant influence on community empowerment,